Association between frailty and hepatic fibrosis in NAFLD among middle-aged and older adults: results from NHANES 2017-2020 - Falide Atabieke; Xiu-Juan Li; Ailikamu Aierken; Jian Li; Yu Zhang; Yierzhati Aizezi; Hong-Liang Gao; Zhi-Qiang Zhang (Frontiers Media S.A., 2024)
BackgroundAlthough previous studies found that frailty is prevalent in NAFLD patients with advanced liver fibrosis and cirrhosis, studies examining the relationship are spare.AimOur study aspires to investigate the potential correlation between the Frailty Index (FI) and hepatic fibrosis among middle-aged and older adults with NAFLD.MethodsData from the 2017-2020.03 National Health and Nutrition Examination Survey (NHANES) were utilized for this study, with a final of 2,383 participants aged 50 years and older included. The quantification of frailty was executed employing a 49-item frailty index. The recognition of hepatic steatosis and fibrosis was accomplished through the utilization of the controlling attenuation parameter (CAP) and transient elastography (TE). The relationship between the FI and hepatic fibrosis were investigated employing univariable and multivariable-adjusted logistic regression analyses. A subgroup analysis was conducted, dividing the subjects based on gender, Body Mass Index (BMI), and the presence of hyperlipidemia.ResultsThe findings demonstrated a positive correlation between the FI and significant hepatic fibrosis in NAFLD, even after using multivariate logistic regression models adjusting for potential confounding factors (OR = 1.022, 95% CI, 1.004-1.041) and in tertiles (Q3vs Q1: OR = 2.004, 95% CI, 1.162-3.455). In the subgroup analysis, the correlation was more statistically significant in male (OR = 1.046, 95% CI, 1.022-1.071), under/normal weight (OR = 1.077, 95% CI, 1.009-1.150), overweight (OR = 1.040, 95% CI, 1.010-1.071), and subjects without hyperlipidemia (OR = 1.054, 95% CI, 1.012-1.097). The area under the Receiver Operating Characteristic (ROC) curve for the FI in assessing the existence of substantial fibrosis in NAFLD was 0.612 (95% CI, 0.596-0.628).ConclusionThis study demonstrated a positive correlation between significant hepatic fibrosis and frailty, particularly among males aged 50 years and older, who were non-obese and did not have hyperlipidemia with NAFLD. Additional studies are required to further validate these findings.